Deformation and Failure Characteristics and Control Technology of Roadway Surrounding Rock in Deep Coal Mines. (22nd September 2020) - Chang, Jucai; Li, Dong; Xie, Tengfei; Shi, Wenbao; He, Kai
Abstract : With the increase in mining depth, the problem of the floor heave of a roadway is becoming increasingly prominent. Solving this problem for a deep high-stress roadway is the key to ensure safe supply and utilization of coal resources in China. This study investigates the floor heave of a horizontal transportation rock roadway at the depth of 960 m at the Xieyi Mine. A four-way loading simulation test frame similar to the Xieyi Mine was used to reproduce the high-stress environment of a deep roadway by loading different pressures on the roof, floor, and two sides of the roadway. The experimental results show that after the tunnel had been excavated, the surrounding rock failure could be divided into three stages: the initial deformation stage, fissure development stage, and mild deformation stage. The destruction time periods of these stages were 0–0.5 h, 0.5–2 h, and 2–6 h, and the destruction ranges were 0.4 m, 1 m, and 1.5 m, respectively. The amount of roof subsidence, the displacement of the two sides, and the floor heave influence each other, and the range of the bearing ring (5.6 m) of the floor is larger than that of the roof (3.4 m) after the surrounding rock has been damaged. The findings suggest that the floor should be supported first, before the two sides and the roof; then, the support of the key parts (roof and floor corners) should be strengthened. The roof, floor, and two sides are considered for controlling the deformation of the surrounding rock in a coupled trinity support mode. Because of the unfavorable conditions in the area, overexcavation backfill technology was used. The new support was successfully applied during the subsequent construction of the rock tunnel. Based on the long-term monitoring results of the surrounding rock deformation, the floor heave control yielded satisfactory results and maintained the long-term stability of the roadway. Therefore, this study can serve as a reference for preventing floor heave in similar high-stress roadways in the future.